Ligation of TLR7 on CD19+CD1dhi B cells suppresses allergic lung inflammation via regulatory T cells. Issue 6 (14th April 2015) - Khan, Adnan R.; Amu, Sylvie; Saunders, Sean P.; Hams, Emily; Blackshields, Gordon; Leonard, Martin O.; Weaver, Casey T.; Sparwasser, Tim; Sheils, Orla; Fallon, Padraic G.
<x xml:space="preserve">Abstract</x> B cells have been described as having the capacity to regulate cellular immune responses and suppress inflammatory processes. One such regulatory B‐cell population is defined as IL‐10‐producing CD19+CD1dhi cells. Previous work has identified an expansion of these cells in mice infected with the helminth, Schistosoma mansoni. Here, microarray analysis of CD19+CD1dhi B cells from mice infected with S. mansoni demonstrated significantly increased Tlr7 expression, while CD19+CD1dhi B cells from uninfected mice also demonstrated elevated Tlr7 expression. Using IL‐10 reporter, Il10−/− and Tlr7−/‐ mice, we formally demonstrate that TLR7 ligation of CD19+CD1dhi B cells increases their capacity to produce IL‐10. In a mouse model of allergic lung inflammation, the adoptive transfer of TLR7‐elicited CD19+CD1dhi B cells reduced airway inflammation and associated airway hyperresponsiveness. Using DEREG mice to deplete FoxP3+ T regulatory cells in allergen‐sensitized mice, we show that that TLR7‐elicited CD19+CD1dhi B cells suppress airway hyperresponsiveness via a T regulatory cell dependent mechanism. These studies identify that TLR7 stimulation leads to the expansion of IL‐10‐producing CD19+CD1dhi B cells, which can suppress allergic lung inflammation via T regulatory cells.